2014
DOI: 10.1177/0037549714540221
|View full text |Cite
|
Sign up to set email alerts
|

A distributed simulation framework for modeling cyber attacks and the evaluation of security measures

Abstract: The aim of this work is to propose a framework for the distributed simulation of cyber attacks based on high-level architecture (HLA), which is a commonly used standard for distributed simulations. The proposed framework and the corresponding simulator, which is called the distributed cyber attack simulator (abbreviated by DCAS), help administrators to model and evaluate the security measures of the networks. At the core of the DCAS is a simulation engine based on Portico, which is an open source HLA run-time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…Another prediction method was presented by Fan et al (2018), which showed an improved integrated cybersecurity prediction method based on spatial-time analysis. Also, with reference to prediction, Ashtiani and Azgomi (2014) proposed a framework for the distributed simulation of cyberattacks based on high-level architecture. Kirubavathi and Anitha (2016) recommended an approach to detect botnets, irrespective of their structures, based on network traffic flow behaviour analysis and machine-learning techniques.…”
Section: General Intrusion Detectionmentioning
confidence: 99%
“…Another prediction method was presented by Fan et al (2018), which showed an improved integrated cybersecurity prediction method based on spatial-time analysis. Also, with reference to prediction, Ashtiani and Azgomi (2014) proposed a framework for the distributed simulation of cyberattacks based on high-level architecture. Kirubavathi and Anitha (2016) recommended an approach to detect botnets, irrespective of their structures, based on network traffic flow behaviour analysis and machine-learning techniques.…”
Section: General Intrusion Detectionmentioning
confidence: 99%
“…Likelihood Est. Univ Georgia,US [45] Bayesian Networks Univ Limerick,IE [123]; George Mason Univ,US [76]; Benedict Coll,US & Univ Illinois,US [69]; Missouri Univ Sci Tech,US [81]; World Islamic Sci Edic Univ,JO & Royal Jordanian Air Forces,JO [ [118] Bounded sensor reading Nanyang Tech Univ,SG [47] Convex Optimization South China Univ Tech,CN [127] Distributed Attack Iran Sci Univ Tech,IR [54] Hierarchical Modeling MIT,US [77] LiSM: Land in Sand Miner NEC Labs Amer,US & Univ Illinois,US & BBN Tech,US [86] Montecarlo Politech Milan,IT & Univ Paris,FR [48] Penetration Testing Malek Ashtar Univ Tech,IR & NIOPDC,IR [26]; US Air Force,US [29] Process Northeastern Univ,CN [128]; Singapore Univ Tech Design,SG & Optiwater,IL & Technion Israel Inst Tech,IL [49]; Shenandoah Res Tech,US [90] Reliability Univ Idaho,US & Texas A&M Univ,US [57] Robust predictive control Northeastern Univ,CN [119] Stochastic Hypothesis Testing Univ Florida,US & Univ Sao Paulo,BR [70] Continued on next page Survey General Shanghai Univ,CN [67]; Univ Hull,UK [92]; MIT,US [82] 6 Analysis and future work…”
Section: Generalmentioning
confidence: 99%
“…They also mentioned previous studies on this issue. Furthermore, [15] presented a simulation of cyberattacks with a distribution approach. Distribution enables people and programs to interact in different geographic locations.…”
Section: Related Workmentioning
confidence: 99%